Pengaruh Promosi Penjualan, Sosial Media Instagram Dan Citra Merek Terhadap Keputusan Pembelian Konsumen - Bagas Dwi Ananta; Sulistiono Sulistiono (Jurnal Ilmiah Pariwisata Kesatuan, 2022)
The purpose of this study was to analyze the EFFECT OF SALES PROMOTION, INSTAGRAM SOCIAL MEDIA, AND BRAND IMAGE ON CONSUMER PURCHASE DECISIONS (Case Study on Kopi Kawan Baru in Bogor City)". Sales Promotion, Instagram Social Media and Brand Image have an important role in making Purchase Decisions. The purposes of this study are (1) to determine the effect of sales promotion on purchasing decisions, (2) to determine social media Instagram on purchasing decisions. (3) To determine the brand image on purchasing decisions. (4). To determine the effect of sales promotion, Instagram social media and brand image together, the number of respondents in this study were 160 respondents who were taken from those who knew and had bought new friends coffee in Bogor City. The research data was processed using SPSS version 26 . The results of this study are as follows: (1) Sales Promotion partially affects purchasing decisions with a t-count value greater than t-table (5.797 > 1.65) and a significant value of 0.000 <0.05; H0 is rejected H1 is accepted. (2) Instagram social media partially influences purchasing decisions with a t-count value greater than t-table (1.753 > 1.65) and a significant value of 0.082 < 0.05; H0 is rejected H2 is accepted. (3) Brand Image partially influences purchasing decisions with a t-count value greater than t-table (5.096 > 1.65) and a significant value of 0.000 <0.05; H0 is rejected H3 is accepted. (4) Sales Promotion, Instagram Social Media, and Brand Image simultaneously have a positive and significant effect on Purchase Decisions with a calculated F value greater than F table ( 94.022 > 2.65 ) and with a significance value of 0.000 and less than (α = 5%) = 0.05. (5) The three independent variables (Sales Promotion, Instagram Social Media, and Brand Image) are able to explain the variation in the dependent variable (Purchase Decision) of 64.4%, while 35.6% of Purchase Decision is influenced by other independent variables.Keywords: Sales Promotion, Instagram Social Media, Brand Image, And Purchase Decision